Industry 4.0/Digitalization and networks of innovation in the North American regional context. Issue 9 (2nd September 2021) - Baker, Paul M.A.; Gaspard, Helaina; Zhu, Jerry A.
ABSTRACT: The advancement of industrial, innovation-related economic policies such as Industry 4.0 and the advanced digitalization of production play an increasingly important role in fulfilling economic objectives in both Canada and the United States. There are a variety of ways in which such industrial-related policy approaches can be developed and implemented. Varying aspects of industrial and economic innovation often occur within a regional context, which can change policy is developed and implemented, dramatically and with little warning. This paper applies a case-based approach to examine enabling and constraining factors of regional innovation policy in two cases - Ontario, Canada and Massachusetts, US. Moving beyond a linear conception of regional innovation, this research explores how policies and modalities for collaboration can facilitate Industry 4.0 and related innovation ecosystems. Our analysis suggests that regional innovation impact is influenced through four principal factors: industrial clusters; context; collaborative synergies; and network intermediaries. Additional research could focus on an expanded case examination of the relationship between top-down policy approaches and the operation of regional innovation ecosystems coupled with bottom-up market- and stakeholderdriven analytic approaches.